1990
DOI: 10.1002/abio.370100508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ensiling on the nutritive value of low quality roughage rice hulls. I. Microbial studies

Abstract: Rice hulls were ensiled in laboratory silos in t w o separate experiments with the same treat. ments. I n the first, sealing was delayed for a period of three days. In the second experiment, silos were sealed immediately after filling. In each experiment, four treatments were applied, namely control, molasses 2% added, urea 0.5% added, and molasses 2% + urea 0.5% added.Lactobacilli, streptococci, and coliforms appear to form the main bulk of the flora characteristic of fresh rice hulls. while the lactic acid b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(10 reference statements)
2
1
0
Order By: Relevance
“…This is in accordance with the findings of SHAWKY et al [20], that the four treatments could be arranged according to their efficiency of enhancing the development of lactic acid bacteria as follows: molasses > molasses + urea > urea > control. This discrepancy can be explained by: (a) The pH values of the molasses-treated rice hulls were lower than those of the untreated rice hulls, which molasses tend to improve the conditions whereby the traditional lactic acid fermentation, with a concomitant fall of pH to 4.8 may take place more readly and with greater certainty, i.e., the lactic acid production was stimulated to some extent, with a corresponding effect on the pH drop.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with the findings of SHAWKY et al [20], that the four treatments could be arranged according to their efficiency of enhancing the development of lactic acid bacteria as follows: molasses > molasses + urea > urea > control. This discrepancy can be explained by: (a) The pH values of the molasses-treated rice hulls were lower than those of the untreated rice hulls, which molasses tend to improve the conditions whereby the traditional lactic acid fermentation, with a concomitant fall of pH to 4.8 may take place more readly and with greater certainty, i.e., the lactic acid production was stimulated to some extent, with a corresponding effect on the pH drop.…”
Section: Discussionsupporting
confidence: 92%
“…It seems clear from these results that the supplementa-tion of 2% molasses can have a beneficial effect on fermentation, resulting not only from increasing the levels of total soluble sugars but also from a direct effect on the activities of the microflora, which is in good agreement with the results of lactobacilli counting in the previous paper according to SHAWKY et al [20], who demonstrated that the prevalence of anaerobic conditions in the presence of molasses provides conditions more favourable for lactic acid bacteria, i.e., the counts reaching 25 x lo6 cells/g on the 90-day period, which runs parallel with the maximum production of lactic acid in the present study. Therefore, the existence and the increase of this acid during the ensiling process was due to the accelerated growth of lactic acid bacteria, which ferment sugars to lactic acid.…”
Section: Discussionsupporting
confidence: 91%
“…Fermented foods and feeds have been consumed by humans and agricultural animals, respectively, for thousands of years (McGovern et al, 2004;Shawky et al, 1990), and the microorganisms that produce them grow in the food (or feed), metabolize nutrients (sugars, amino acids, etc. ), and produce metabolites that humans (or animals) find desirable in terms of flavor, aroma, texture, etc.…”
Section: Food and Feed Fermentationmentioning
confidence: 99%